Pregnancy Tradition "Ngapati" in Javanese Society Based on Perspective of the Qur'an and Hadith - Aliyah, Himatul; Jannah, Roudlotul; Azizah, Nilatul (Journal Intellectual Sufism Research (JISR), 2020)
Traditions and customs are an inseparable part of Javanese society. Traditipns four months of pregnancy or known as ngapati is one of the traditions carried out by the Javanese people until now. But nowadays, the tradition of ngapati is much abandoned by the Society. Some people consider the tradition to be out of order in the Qur'an and the Hadith, and even prohibit it. By comparing various exposures from the literature, the authors analyze, identify and review many literatures, this article discusses in depth the tradition of ngapati done by the community and its relation in the Qur'an and Hadith. Research reveals that the tradition of the regent is not in conflict with the Qur'an and the Hadith.